In-house Contractors’ Exposure to Risks and Determinants of Industrial Accidents; With Focus on Companies Handling Hazardous Chemicals - Shin, Kyusoo (Saf Health Work, 2021)
BACKGROUND: The series of serious industrial accidents in recent years at contractors to large companies has highlighted risk outsourcing as a real and urgent problem. This study aims to review the difference in the degree of risk exposure and the occurrence of industrial accidents depending on the type of company relations. Among in-house contractors, the focus will be on those handling hazardous chemicals that include companies for which outsourcing requires approval. METHODS: This study uses the 9th wave of the Industrial Safety and Health Survey (2018). For determining the degree of risk exposure, the occurrence of industrial accidents, and industrial accident rate, multivariate, logistic, and fractional logit, regression analyses were used, respectively. RESULTS: First, In-house contractors’ degree of risk exposure is higher than that of the client companies. In particular, this gap is even greater for companies dealing with chemicals. Second, among only those that handle hazardous chemicals, in-house contractors do show a significantly higher rate of industrial accident occurrence. Third, In-house contractors have a significantly higher rate of industrial accidents from diseases than client companies. CONCLUSION: The analysis supports the intent of the legal amendment that strengthens the protection of in-house contracted workers who handle hazardous chemicals. Second, the results of this study suggest that safety and health management must go beyond legal compliance and ensure that it has substance and effectiveness. Last, there should be policy consideration is necessary to reduce attempts to hide industrial accidents.